Performed a Qualitative and Quantitative of Breast Self-Examination: a Checklist Approach - Mahshid Bokaie; Mohammad Hassan Lotfi (Shahid Sadoughi University of Medical Sciences, 2013)
Introduction: Breast neoplasia is the most common cancer among women in both developed and developing countries. Over 1.15 million women in the world detecting with breast neoplasia each year and the mortality rate is 502,000 cases from this cancer. The purpose of this study was to describe how Iranian women perform breast self-examination. Materials and methods: In this cross-sectional study 447 participants referred to five health center of Shahid Sadoughi University of Medical Sciences were chosen. The questionnaire and checklist were completed by all participants through a face-to-face interview. If she obtains 0-6 total score, she has weak performance, if she obtains 7-12 total score, she has acceptable performance and if she obtains 13-18 total score, she has good performance of breast self-examination. Statistical analysis carried out using Statistical Analysis Software (SAS) version 16. A P-value of <0.05 was considered statistically significant. Non-parametric tests such as Mann-Whitney were adopted. Results: In our study, 92% of women heard about breast self-examination, but only 17.4% of them performed it monthly. Of 447 participants, 348 (77.9%) had poor, 78 (17.4%) moderate and only 21 (4.7%) had good performance. From all participants, 189(42%) by health worker, 36(8.1%) by family and 70(15.7%) by media learned how to perform breast self-examination. Conclusion: The study showed that although most of women heard about breast self-examination but it was not a routine screening in developing country. This study confirmed that Iranian women have poor knowledge about how to perform breast self-examination. There is need for adequate health education on breast cancer and breast self-examination among Iranian women.